Human Resources Projection on Business planning PT. Franchise Center Indonesia - Manu, Bheryl; Rahmat Syah, Tantry Yanuar; Iskandar, Muhammad Dhafi; Abadi, Ferryal (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The strategic planning process that must be carried out by organizations is to be able to develop and align human resource management policies and practices for organizational success. The aim of this service is to create human resource planning to determine the organization's needs in terms of employee quality and quantity. This research on human resource planning using qualitative research methods is intended to obtain more comprehensive information regarding the strategic planning process which is integrated with business planning. By analyzing the data and documents found as well as the researcher's interpretation, it can be concluded that research on strategic human resource planning at PT. FCI, from planning to implementation and evaluation, is in accordance with planning and strategy theories and concepts, such as HR planning which has been integrated with business planning outlined in short-term and medium-term targets. When planning human resource management, more attention should be paid to facilities and infrastructure so that activities in human resource planning can be carried out well.